Does arthroscopy cause more complications than arthrocentesis in patients with internal temporomandibular joint disorders? Systematic review and meta-analysis - Nogueira, E. F.C.; Lemos, C. A.A. [UNESP]; Vasconcellos, R. J.H.; Moraes, S. L.D.; Vasconcelos, B. C.E.; Pellizzer, E. P. [UNESP] (Elsevier, 2021)
The objective of this study was to compare, through a systematic review with a meta-analysis, the relative risks of arthroscopy and arthrocentesis in the temporomandibular joint. MEDLINE/PUBMED, EMBASE, Cochrane Library (CENTRAL), Web of Science, SCOPUS were the researched databases, as well as grey literature and manual searches. The search results showed 656 studies, but only five met the eligibility criteria. The evaluation included 194 joints (104 patients): 101 were arthroscopy and 93 arthrocentesis. Complications were observed in four patients undergoing arthroscopy (two with temporary facial paralysis and two with prolonged cervical oedema) and in three patients undergoing arthrocentesis (two with severe bradycardia and one with prolonged cervical oedema). The meta-analysis demonstrated a relative risk of 0.99 for complications after arthroscopy compared with arthrocentesis, but the results showed no statistical differences. In conclusion, this systematic review suggests that there is no increased risk of complications with arthroscopy than arthrocentesis. When complications were present, they were temporary.
Keywords: arthrocentesis; arthroscopy; Temporomandibular joint